Authoritarian nightmare : Trump and his followers - Dean, John W. (John Wesley), 1938-; Altemeyer, Bob, 1940- (Melville House, 2020)
"How did America end up with a leader who acts so crudely and despotically, and counter to our democratic principles? Why do his followers stick with him, even when he acts against their own interests? To fully understand, John Dean, a man with a history of standing up to autocratic presidents, joined with Bob Altemeyer, a professor of psychology with a unique area of expertise: Authoritarianism. Relying on social science findings and psychological diagnostic tools (such as the "Power Mad Scale" and the "Con Man Scale"), as well as research and analysis from the Monmouth University Polling Institute (one of America's most respected public opinion research foundations), the authors provide us with an eye-opening understanding of the Trump phenomenon -- and how we may be able to stop it." --